Nghiên cứu xây dựng makét niên giám thống kê theo hệ thống chỉ tiêu thống kê quốc gia - Đậu, Ngọc Hùng (2011)
Tác giả: Đậu Ngọc Hùng, CN; Nguyễn Thị Chiến, CN; Nguyễn Thị Ngọc Vân, CN; Phạm Tiến Nam, CN; Nguyễn Thu Oanh, CN -- Từ khóa: Niên giám thống kê